Cross-sectional study of the prevalence of inter-arm blood pressure difference in offspring of normotensive and hypertensive parents among students of tertiary care teaching hospital, Hyderabad - Prashanthi M; Santa Kumari A; Abdul Raoof Omer Siddiqui; Mudassir Mirza (Asian Journal of Medical Sciences, 2024)
Background: Hypertension (HTN) incidence and progression are monitored by regular blood pressure (BP) measurement; one of the most ignored components of regular check-up is the measurement of inter-arm difference (IAD) in BP. Aims and Objectives: The objective of this study was to estimate the prevalence of IAD in BP among offspring of hypertensive parents compared to normotensive parents. Materials and Methods: This cross-sectional study was conducted on 100 male students at Osmania Medical College, Hyderabad, Telangana for a period of 6 months. After IEC clearance, the subjects were divided into two groups, 50 students in each group: Group I had offspring with hypertensive parents and Group II had offspring with normotensive parents. Age, height, weight, and body mass index (BMI) were recorded. IAD was calculated as the difference between BP (Systolic BP [SBP] and diastolic BP [DBP]) in the right arm and left arm. Subjects with a history of structural, functional cardiovascular disease disorders, endocrine disorders, Diabetes mellitus, and addictions such as smoking and alcohol were excluded from the study. Data were statistically analyzed using Microsoft Excel software. Results: Among 100 subjects, Group I and II IAD in SBP was 8.68±6.02 and 5.00±3.24 (P<0.0002), respectively, and Group I and II IAD in DBP was 5.12±4.48 4.79±3.56 (P<0.7117), respectively. BMI of the two groups is almost within the similar range (23.44±4.04, 22.098±3.15, respectively) and not statistically significant (P=0.0694), a positive correlation of 0.12, 011 was found between BMI, systolic IAD,and diastolic IAD, respectively. Conclusion: The above results show a significant association between IAD in systolic BP and family history of HTN.